PROSPECTS AND PROBLEMS OF WAQF IN INDONESIA - Caniago, Muhammad Ali Imran; Satibi, Ibi (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2024)
The aim of this research is to describe the prospects and problems of waqf in Indonesia. This research uses descriptive qualitative methods. The research results show that Waqf in Indonesia has quite large potential, in 2022 there will be 440,512 points of waqf land in Indonesia with a total area of 57,263.69 hectares. If these assets are used productively, the potential is very large, around 19.4% of Indonesia's gross domestic product. Apart from that, the potential for cash waqf is estimated to reach 180 trillion rupiah per year. Apart from the great potential, there are problems with waqf in Indonesia, namely: Nadir's low understanding of waqf principles, law, management and Nadir's profession not yet being the main profession are the causes of the low quality of Nadir's waqf in Indonesia. Apart from that, Wakif's limited understanding of the concept, law and objectives of waqf is also part of the problems of waqf in Indonesia. Likewise, low public knowledge about waqf causes waqf assets in the community to not be managed well and productively. Waqf management in Indonesia tends to be traditional, the waqf certification process is complicated, coordination between institutions is weak, the use of waqf assets is not yet productive, government policies and supervision regarding the use of existing assets are not optimal, thus causing conflicts over waqf land.